Reaction Coronas at Olivine–Plagioclase Contacts in Host Rocks from the Nova–Bollinger Ni–Cu–Co Deposit, Albany–Fraser Orogen, Western Australia: Evidence of a Magmatic to Metamorphic Continuum. (21st June 2021) - Torres-Rodriguez, Natalia; Barnes, Stephen J; Taranovic, Valentina; Pearce, Mark A; Verrall, Michael; Schoneveld, Louise E
Abstract: A prominent feature of the cumulate rocks of the Nova intrusions is the presence of reaction coronas between olivine and plagioclase. A particular spatial arrangement of mineral textures, typical of olivine–plagioclase coronas in high- P troctolites and olivine gabbros worldwide, is almost universally observed: partially resorbed olivine with a cuspate margin, surrounded by orthopyroxene, surrounded by a zone of symplectite comprising hornblende + clinopyroxene, orthopyroxene and Cr-poor Al–(Fe, Mg) spinel, with a cuspate boundary against plagioclase. Where amphibole-free clinopyroxene–spinel symplectite is developed it is typically as an outer layer against plagioclase. The mineralogy and composition of these coronas has been revealed by a combination of scanning electron microscopy and synchrotron X-ray fluorescence microscopy. There is a close spatial association between reaction symplectites and Bowen reaction series sequences developed by reaction between cumulus phases and fractionated trapped interstitial melt, giving rise to local Cr and Ti enrichment within the coronas relative to olivine and plagioclase, accompanying enrichment in water recorded by stabilization of amphibole. These relationships imply that trapped liquid crystallization and corona formation were part of a process continuum, such that the coronas record mineral reactions close to the solidus temperature of the cumulates, initially developing in the presence of evolved hydrous interstitial liquid and continuing to develop in the solid state below the solidus. The symplectites owe their fine microstructure to diffusion-limited growth of the products of solid-state reactions below the solidus. The initial magmatic stage of corona formation records conditions of 0·76 and 0·96 GPa and around 1035 °C based on THERMOCALC pseudosections calculated for the bulk composition of the corona assemblage. Two-pyroxene assemblages within the symplectites record temperatures around 850–900 °C and pressures between 0·7 and 1·1 GPa. These pressure estimates are in good agreement with those obtained from regional metamorphism studies of the country rock paragneisses, confirming independent lines of evidence that the Nova intrusions were syn-metamorphic, emplaced under granulite-facies peak metamorphic conditions at crustal depths of 28–35 km. The unusually extensive development of the symplectites reflects the cooling history of the intrusions, which remained at temperatures close to solidus temperatures on the timescale of regional tectonic uplift and cooling of the deep roots of the orogen.